Rol familiar y el rendimiento académico de los estudiantes del segundo nivel de secundaria en la Institución Educativa Nº 60276 Eugenio Rivera distrito de Yavarí, provincia Mariscal Ramón Castilla 2023 - Romo Rojas, Elfi Janeci (2024)
This research was carried out with the purpose of resolving the following question: To what extent is the role of parents related to the academic performance of the students of the second level of secondary school at the Eugenio Rivera López Educational Institution, district of Yavarí, province of Ramón Castilla 2023?, admitting that its main objective is to determine the relationship that exists between the role of parents and the academic performance of the students of the second level of secondary school of the Eugenio Rivera López educational institution, district of Yavarí, province of Ramón Castilla 2023.The methodology adopted in the research is transactional in nature, with a quasi-experimental design and a correlational and transversal descriptive nature. The selected population and sample consisted of 30 2nd grade students from the Eugenio Rivera López educational institution in the Yavarí district. The survey was used as a technique and instrument, respectively, to obtain data, both were supported by expert validation. The analysis of the information included descriptive techniques such as frequency, average and percentage analysis, as well as an inferential analysis to evaluate the proposed hypotheses. The study design was cross-sectional, descriptive-correlational and non-experimental. As a main conclusion, it was found that there is a significant relationship between parental participation and the academic performance of the students of the second level of secondary school of the Eugenio Rivera López educational institution, district of Yavarí, province of Ramón Castilla 2023.